Bio-nanoparticles sensor couple with smartphone digital image colorimetry and dispersive liquid–liquid microextraction for aflatoxin B1 detection - Mahsa Alikord; Nabi Shariatifar; Mammad Saraji; Hedayat Hosseini; Gholamreza Jahed Khaniki; Shahram Shoeibi; Toba Rezazadeh; Mohammad Fazeli (Scientific Reports)
Abstract A novel nanobiosensor-based colorimetric method was developed by integrating ZnO nanoparticles functionalized with curcumin, dispersive liquid–liquid microextraction (DLLME), and smartphone digital image colorimetry for the sensitive detection of aflatoxin B1 (AFB1) in baby food samples. The unique combination of biologically-derived ZnO nanoparticles with curcumin created a sensing platform, while DLLME provided efficient pre-concentration of the target analyte. A custom-designed portable colorimetric box enabled standardized image capture and analysis using a smartphone camera and colorimetric software. Under optimized conditions using chloroform as the extraction solvent and acetonitrile as the disperser solvent, the method achieved a remarkable limit of detection of 0.09 μg/kg within linear concentration range of 0–1 μg/L. The calibration curves demonstrated excellent linearity (R2 > 0.9906) with high precision (RSD < 5.52%). The method was successfully validated using baby food samples, achieving high recoveries (89.8–94.2%). This innovative integration of nanobiosensing, microextraction, and smartphone technology offers a rapid, highly sensitive, and cost-effective platform for on-site AFB1 detection in food safety applications, particularly beneficial for resource-limited settings.